"The Impact of Information on Foreign Policy Decision-Making" (Tikrit Journal For Political Science, 2016)
The research aims at showing the impact of information in the process of foreign political decision-making through shedding light on the role that information play in each stage of decision-making. The research falls into two sections،, the first one tackles the foreign political decision-making process، whereas the second one studies the impact of information in the process of foreign political decision-making. The researcher has come up with some results that clarifies the general framework of the role that information play in the process of foreign political decision-making.
Keywords: • Information • Decision-making • External political decision • Foreign policy • Impact • Influence • Political decision • External decision • Diplomatic decision • Information analysis